2010
DOI: 10.1128/mcb.01040-09
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Prion Protein Promotes Regeneration of Adult Muscle Tissue

Abstract: It is now well established that the conversion of the cellular prion protein, PrP C , into its anomalous conformer, PrP Sc , is central to the onset of prion disease. However, both the mechanism of prion-related neurodegeneration and the physiologic role of PrP C are still unknown. The use of animal and cell models has suggested a number of putative functions for the protein, including cell signaling, adhesion, proliferation, and differentiation. Given that skeletal muscles express significant amounts of PrP C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 75 publications
(97 reference statements)
3
46
0
3
Order By: Relevance
“…Up to date, de Vries et al (2004) proved significant effects for the PrP genotype on both conformation score in Texel sheep and muscle mass score in German Black Headed Mutton sheep. In addition, Stella et al (2010) found that the PrPs control the release of TNF-α factor which involved in muscle differentiation and downstream signalling pathways that affect the longevity of cells in adult muscles in many species of mammals; Smith et al (2011) cited that the low level of PrP is associated with decreased muscle mass of rat. Isler et al (2006) showed a correlation between the variation in PrP genotypes and the longissimus muscle depth of Dorset × Romanov sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, de Vries et al (2004) proved significant effects for the PrP genotype on both conformation score in Texel sheep and muscle mass score in German Black Headed Mutton sheep. In addition, Stella et al (2010) found that the PrPs control the release of TNF-α factor which involved in muscle differentiation and downstream signalling pathways that affect the longevity of cells in adult muscles in many species of mammals; Smith et al (2011) cited that the low level of PrP is associated with decreased muscle mass of rat. Isler et al (2006) showed a correlation between the variation in PrP genotypes and the longissimus muscle depth of Dorset × Romanov sheep.…”
Section: Discussionmentioning
confidence: 99%
“…13 To obtain this data, our strategy considered the use of an in vivo paradigm novel to the field of PrP C biology. It consisted in acutely damaging the hind limb tibialis anterior muscle of adult mice expressing or not PrP C , and then in following regeneration from muscle precursors cells.…”
Section: Promotes Regeneration Of Adult Skeletal Musclementioning
confidence: 99%
“…Наприклад, показано, що у PrP-нокаутованих мишей порушений процес утворення гемопоетичних лімфоци-тів [112] і пригнічена регенерація скелетних м'язів [94].…”
Section: +unclassified